IMPLIKASI KURIKULUM 2013 TERHADAP PROSES BELAJAR MENGAJAR - Mustofa, Mustofa (Universitas Pendidikan Indonesia, 2014)
The curriculum is one element that can make a significant contribution to realizing the potential quality of the development process of students, the curriculum is seen as a book or a document that is used as a guidance teacher in the learning process. Without appropriate curriculum will be difficult to achieve the goals and desired educational goals. In Indonesia has beberapakan held curriculum change and curriculum improvement. This change is held to realize the national development in the field of education. Changes that arise will certainly have implications for teaching and learning activities. How is the implication is the purpose of the writing of this paper. Implications of the implementation of the curriculum in 2013 can be viewed positively and negatively and was indeed the teacher plays an important role for the implementation of Curriculum 2013 and look at the shape and the process of change as a constructive. Keywords: curriculum 2013, teacher, teaching and learning.